Boundary-element analysis of the dynamic state of piecewise homogeneous elastic bodies using convolution quadratures - Amenitskiy, Alexandr Vladimirovich; Belov, Alexandr Alexandrovich; Igumnov, Leonid Alexandrovich; Litvinchuk, Svetlana Yurievna (Computational Continuum Mechanics, 2008)
An approach to the analysis of 3-D dynamic problems of elasticity for piecewise homogeneous bodies using a BEM explicitly accounting for the time variable is presented. The boundary-element scheme of constructing a discrete analogue is used in combination with the convolution quadrature method. A novel scheme of the convolution quadrature method is constructed. The results of the BEM analysis are presented. The developed BEM-scheme is shown to be highly accurate.